Mean platelet volume in euthyroid patients with Hashimoto's thyroiditis. Issue 3 (April 2015) - Carlioglu, Ayse; Timur, Ozge; Durmaz, Senay A.; Ayhan, Mehmet E.
Abstract : Mean platelet volume (MPV) is the measure of platelet size. MPV possibly is a simple way to estimate platelet activity. In this study, we aimed to investigate MPV levels in euthyroid Hashimoto's thyroiditis patients. Fifty-one euthyroid patients with Hashimoto's thyroiditis attending our outpatient clinic of the endocrinology department, and 51 age and BMI-matched healthy individuals were included in this study. All patients with euthyroid Hashimoto's thyroiditis were at euthyroid state. None of the study patients was subjected to levothyroxine replacement therapy. Anti-thyroid peroxidase (anti-TPO) antibody and anti-tiroglobulin antibody were positive. All the study participants were evaluated by biochemical and platelet parameters. There were no significant differences in age (33.88 ± 12.87 and 30.18 ± 12.43 years, respectively; P  > 0.05) and BMI (23.55 ± 3.34 and 22.25 ± 3.65 kg/m 2, respectively, P  > 0.05) between the study and the control groups. Anti-TPO and anti-tiroglobulin levels were significantly higher in the study group (anti-TPO 428.32 ± 668.39 IU/ml in the euthyroid Hashimoto's thyroiditis group; 14.85 ± 9.66 IU/ml in the control group, P  = 0.001; anti-tiroglobulin 320.46 ± 796.05 IU/ml in the euthyroid Hashimoto's thyroiditis group, 21.28 ± 26.24 IU/ml in the control group, P  = 0.09). There were no significant differences in terms of serum thyroid-stimulating hormone (TSH) (1.76 ± 0.79 and 1.85 ± 1.14 uIU/ml, respectively), FT3 (3.10 ± 0.37 and 3.29 ± 0.76 pg/ml, respectively) and FT4 (1.22 ± 0.42 and 1.46 ± 0.78 pg/ml, respectively) levels between the study and the control groups. Serum triglyceride levels were significantly higher in the study group than in the control group (133.81 ± 91.50 and 90.18 ± 41.15 mg/dl, respectively; P  = 0.015). Mean MPV levels were significantly higher in the euthyroid Hashimoto's thyroiditis group than in the control patients (8.8 ± 1.05 and 7.9 ± 0.79 fl, respectively; P  = 0.0001). To assess the correlation with MPV, a Pearson's correlation analysis was performed on each variable. There were positive correlations between anti-TPO and MPV levels ( r  = 0.246, P  = 0.042), and between anti-tiroglobulin and MPV levels ( r  = 0.256, P  = 0.033). The multiple regression analysis of MPV and other risk factors was performed. Age, BMI, C-reactive protein and waist circumference were independent predictive factors of MPV. Adjustment for other factors did not alter these relative risks. Our results suggest that even if in euthyroid state, patients with euthyroid Hashimoto's thyroiditis have higher MPV levels than the healthy controls. As higher MPV levels are closely related with cardiovascular diseases, euthyroid Hashimoto's thyroiditis patients have greater risk of atherothrombotic complications than controls.